Penguin Café Orchestra, Malcolm and Mary: The soundtrack of Melbourne's outcast children. Issue 2 (1st August 2019) - Sandars, Diana
The 1970s and 1980s inner suburbs of Melbourne, Australia, in Malcolm (Tass, 1986) and Mary and Max (Elliot, 2010) are places of banality and imprisonment that beg for imaginative escape. This article argues that the distinctive Penguin Café Orchestra (PCO) music on the soundtracks of both films defines, facilitates and celebrates this escape as a product of a child's imaginary. The shared use of PCO in both films creates a lingua franca between the titular characters of each film and a Melbourne that is redefined in these imaginary spaces by characters it ultimately cannot contain. In contrast to the liberatory and irrational pleasures of child's play in Malcolm, in Mary and Max PCO connotes a wonderment borne from an entrapment in disappointment and loneliness. The need to contain the imaginary of Melbourne's outcast daughter, unlike its son, is rendered explicit through the use of Barry Humphries' voice-over narration.